Reflections of Yin-Yang Philosophy on Space Design and Analysıs Through Examples (Journal of Interior Design and Academy, 2023)
While communicating with users, spaces should include concepts such as creativity, originality and aesthetics. At this point, designers bring design solutions by understanding the lifestyles and the image formed in the user's mind while providing communication between the user and the space. It can be said that the concept of design, which can be expressed as an act of human consciousness, covers the needs in the material and spiritual world and is shaped within this framework. While the concept described as the material world is expressed as a concrete example of space design, the spiritual world includes the vital philosophies of the sociocultural structure and its reflections on design. Yin-Yang, an ancient Chinese philosophy, is a cultural thought and philosophy in the Far East. This philosophy shapes people's social lives and also their lifestyles. In this study, a literature study was conducted and visual techniques were utilized to investigate the place and importance of Yin-Yang philosophy on space design. As a result of the analysis of the visual data obtained, it was seen that Yin-Yang philosophy has an impact on space design as well as being a spirituality or a way of life.
Keywords: Space design; design, user-space interaction; cultural reflection; yin-yang philosophy